Population structure of podocnemis expansa (Testudines: Podocnemididae) in Southern Brazilian amazon - Costa Gonçalves Portelinha, Thiago (2014)
Detailed studies of the population structure of most species of turtles in the Amazon Basin are lacking throughout their range. We estimated sex ratio, size structure, relative abundance, and recapture index for the Giant South American River Turtle (Podocnemis expansa) in Javaés River, southern Brazilian Amazon. Field work was conducted between 2004 and 2009, and comprised a total sampling effort of 368 hours in 92 sampling days. Turtles were captured by diving and seining. A total of 645 individuals (156 adult males, 109 adult females, and 380 juveniles) were captured and marked, but only five were recaptured. Carapace length showed a unimodal pattern for males, but no clear pattern for females. The population consisted predominantly of adult males and young females, with a sex ratio of 1.4:1 (M:F). Relative abundance varied from 0-5.5 animals/h depending on the capture method employed. Most animals (73.7%) were concentrated in a single location on the river (1 km out of 40 km sampled) during the study period. Population monitoring on a long-term basis will be necessary to identify the real population structure, evaluate poaching pressure, and to support the conservation project which has been ongoing since 1985 in the area.